A 0.123% Stevia/Aspartame 91/9 Aqueous Solution Balances the Effects of the Two Substances, and may thus be a Safer and Tastier Sweetener to be Used - Marie-Claire Cammaerts; Roger Cammaerts; Axel Dero (Journal of Pharmacy and Nutrition Sciences, 2015)
Sweeteners are presently largely consumed all over the world, essentially aspartame (North America, Europe) and stevia (South America, Asia). Aspartame has a pleasant taste but present some adverse effects; stevia has very few adverse effects but has not the sweetest taste. Using ants as biological models, we here examined if a 0.123% solution of stevia/aspartame 91/9 might have both a pleasant taste and nearly no adverse effects. We found that it did not change the ants’ food consumption while aspartame increased it and stevia slightly decreased it. It did not affect their locomotion, precision of reaction and response to pheromones as aspartame did. It did not increase their audacity as aspartame largely and stevia somewhat did. It did not affect the ants’ brood caring behavior and cognition as aspartame did, and it did not impact the conditioning ability and memory as aspartame drastically and stevia slightly did. Confronted to sugar water and a stevia/aspartame 91/9 solution, the ants equally drunk the two solutions, while having the choice between aspartame and sugar, they soon nearly exclusively chose the sugar, and while in presence of stevia and sugar, the ants progressively chose the sugar. Very probably aspartame enhanced the taste of stevia, and as the latter contains a true glycoside, a stevia/aspartame 91/9 solution did not affect the ants’ physiology and ethology as pure aspartame did. In front of sugar and a stevia/aspartame ca 96/4 solution, the ants chose the sugar. Thus, a 0.123% solution in which 9% aspartame (and no less) is mixed to 91% stevia (and no more) appears to constitute a safe and tasty sweetener which could be used instead of solutions containing only aspartame or stevia.